Analysis of practices in childbirth and postpartum hospital care - Nivea Alane dos Santos Moura; Viviane Rolim de Holanda; Geyslane Pereira Melo de Albuquerque; José Flávio de Lima Castro; Hemelly Raially de Lira Silva; Elizama Paula Gomes da Rocha (Universidade Federal do Ceará, 2020)
Objective: to analyze practices in childbirth and postpartum hospital care. Methods: cross-sectional study, conducted with 335 mothers in a reference maternity hospital. A form was used based on the indicators of the Bologna index and guidelines for childbirth and puerperium assistance. Data were analyzed using descriptive and inferential statistics (chi-square, binomial and Clopper-Pearson tests), with p<0.05 being significant. Results: it was observed that 77.9% of the puerperal women considered professional assistance satisfactory. The presence of the doula (p=0.037) and breastfeeding in the first hour of life (p=0.032) had a significant relation with the evaluation of women. The Bologna index evaluation obtained an average of 2.6. Conclusion: there was a higher frequency of intermediate and inadequate practices in childbirth and postpartum care.